1,1′-Butylenebis(3-sulfo-3H-imidazol-1-ium) hydrogensulfate: a versatile task-specific ionic liquid catalyst for the synthesis of 4H-pyran scaffolds through non-conventional process - Khaligh, Nader Ghaffari; Ong, Chiu Ling; Mihankhah, Taraneh; Johan, Mohd Rafie; Juan, Joon Ching (Springer Verlag, 2019)
Abstract: In the present study, the catalytic efficiency of 1,1′-butylenebis(3-sulfo-3H-imidazol-1-ium) hydrogensulfate (BBSI-HSO 4 ) as a versatile sulfonic acid-functionalized ionic liquid was demonstrated for the one-pot mechanosynthesis of pyrano[4,3-b]-pyrans using planetary ball mill at room temperature under solvent-free conditions. This efficient mechanosynthesis approach to the 4H-pyran scaffolds displays a combination of the structure–activity relationship of ionic liquids with ecological benefits of a mechanocatalytic procedure. The ionic liquid was easily recycled and reused several times with no significant loss of its catalytic activity. Graphical abstract: [Figure not available: see fulltext.]. © 2019, Springer-Verlag GmbH Austria, part of Springer Nature.